Memory and Landscape Indigenous Responses to a Changing North - Pratt, Kenneth L.; Heyes, Scott A. (Athabasca University Press, 2022)
The North is changing at an unprecedented rate as industrial development and the climate crisis disrupt not only the environment but also long-standing relationships to the land and traditional means of livelihood. Memory and Landscape: Indigenous Responses to a Changing North explores the ways in which Indigenous peoples in the Arctic have adapted to challenging circumstances, including past cultural and environmental changes. In this beautifully illustrated volume, contributors document how Indigenous communities in Alaska, northern Canada, Greenland, and Siberia are seeking ways to maintain and strengthen their cultural identity while also embracing forces of disruption. Indigenous and non-Indigenous contributors bring together oral history and scholarly research from disciplines such as linguistics, archaeology, and ethnohistory. With an emphasis on Indigenous place names, this volume illuminates how the land-and the memories that are inextricably tied to it-continue to define Indigenous identity. The perspectives presented here also serve to underscore the value of Indigenous knowledge and its essential place in future studies of the Arctic. Contributions by Vinnie Baron, Hugh Brody, Kenneth Buck, Anna Bunce, Donald Butler, Michael A. Chenlov, Aron L. Crowell, Peter C. Dawson, Martha Dowsley, Robert Drozda, Gary Holton, Colleen Hughes, Peter Jacobs, Emily Kearney-Williams, Igor Krupnik, Apayo Moore, Murielle Nagy, Mark Nuttall, Evon Peter, Louann Rank, William E. Simeone, Felix St-Aubin, and Will Stolz.